Disjunctive realism about color - De Mey, Tim (Problems from Armstrong, 2008)
Section 1: Analytical metaphysics and its methodology. Why the negations of false atomic propositions are true / Peter Simons – The one over many / Anna-Sofia Maurin – Armstrong's conception of supervenience / Markku Keina\unmatched{0308}nen – ˝Mirage realism˝ or ˝Positivism in naturalism's clothing˝? / Panu Raatikainen – Armstrong's metaphysical realism / Sami Pihlstro\unmatched{0308}m. Section 2: Laws of nature, dispositions, and modality. Some remarks on the metaphysical status of laws of nature / Wim Christiaens – Dispositions pace Armstrong / Robrecht Vanderbeeken – Armstrong on the metaphysics of modality: two dilemmas / Anssi Korhonen. Section 3: Mind and epistemology. Disjunctive realism about color / Tim De May – On Armstrong's philosophy of perception / S. Albert Kivinen – Armstrong's epistemology / Markus Lammenranta.